2019
DOI: 10.1002/aic.16800
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating CO2 capture of highly permeable polymer through incorporating highly selective hollow zeolite imidazolate framework

Abstract: The implementation of high-performance membranes in large-scale CO 2 capture has the potential to significantly decrease the capture cost and reduce the environmental footprints. However, highly permeable polymers rarely have sufficient selectivity for energy-efficient carbon capture. In this study, zeolite imidazolate framework hollow nanoparticles (ZIF-HNPs) were synthesized and embedded into highly permeable polymers as versatile fillers to prepare mixed matrix membranes (MMMs). The interior hollow architec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…For the comparison shown in Fig. 5a, only literature studies reporting (1) pure-gas permeability measured at a pressure consistent with the CO 2 partial pressure reported for the mixed gas test, and ( 2 values than backbones containing groups such as -F, -H, or -CN 18,23,35,[92][93][94][95][96][97] . Moreover, all polymers considered from the literature have below 5.5 and a less than 1.5.…”
Section: Comparisons To Other Microporous Polymersmentioning
confidence: 81%
“…For the comparison shown in Fig. 5a, only literature studies reporting (1) pure-gas permeability measured at a pressure consistent with the CO 2 partial pressure reported for the mixed gas test, and ( 2 values than backbones containing groups such as -F, -H, or -CN 18,23,35,[92][93][94][95][96][97] . Moreover, all polymers considered from the literature have below 5.5 and a less than 1.5.…”
Section: Comparisons To Other Microporous Polymersmentioning
confidence: 81%
“…Introduction of additives such as nanoparticles and microporous organic fillers has also been among the promising approaches for inhibition of aging. Mixed matrix membranes (MMMs) based on PIM-1 and various organic and inorganic fillers have been studied for gas separation. Inclusion of certain fillers, such as functionalized graphene and graphene oxide (GO), hyper-cross-linked polymer (HCP), and polyaromatic framework (PAF-1) has shown promising effects toward impeding or even ending aging. It has been shown that the similar composition of nanoporous organic fillers, or more specifically the aryl-H groups of PAF-1 and methyl groups of PIM-1 and PTMSP, result in formation of molecular interactions at the interface and therefore an antiaging effect in the MMMs …”
Section: Introductionmentioning
confidence: 99%
“…Membrane technology has extensively shown its merits in gas separation in the last decade 8 . Mixed‐matrix membranes (MMMs) combine the advantages of polymer dense membranes and porous membranes and, as a result, have attracted great attention 9 . As a porous crystalline material with organic linkers and metal ions, MOFs are widely used as fillers because of their ultrahigh specific surface area, high porosity, high affinity for gas molecules, and adjustable pore size 10 …”
Section: Introductionmentioning
confidence: 99%